An opt‐out model for kidney transplant referral: The time has come. Issue 1 (5th July 2020) - Huml, Anne M.; Sedor, John R.; Poggio, Emilio; Patzer, Rachel E.; Schold, Jesse D.
Abstract : Disparities that affect equity in access to kidney transplantation for patients with kidney failure have been well described. Many robust clinical trials have tested the effectiveness of interventions to reduce disparities and equilibrate access to kidney transplantation. Moreover, policy changes have been enacted to achieve the same aims. Despite these efforts, rates of kidney transplant waitlisting within the first year of end‐stage kidney disease have remained unchanged over the past 2 decades, while incident rates of end‐stage kidney disease have climbed. Because prior interventions have not durably increased transplant access, disruptive change is clearly needed. The Advancing American Kidney Health Executive Order sets bold goals to transform kidney care for patients and caregivers. In this spirit, we discuss an Opt‐Out for Transplant Referral Model as a compelling solution to improve equity in access to kidney transplantation. Abstract : An opt‐out for transplant referral model is a compelling solution to improve equity in access to kidney transplantation.